Comparative Study on Physical Fitness between Indigenous and Non-indigenous Students - Chiluwal, Shailandra (Interdisciplinary Research in Education, 2021)
Physical fitness is essential for all. This is comparative cum cross-sectional study dealing with the physical fitness of students. It was conducted in the secondary schools of Lamjung district with the objective to compare the physical fitness between indigenous and non- indigenous students. Altogether 150 secondary level male students were selected as the respondents consisting 75 for each group. Five schools were selected using purposive sampling method whereas, the respondent students were selected using purposive cum random sampling method. American Association for Health, Physical Education and Recreation (AAHPER) Youth Physical Fitness Test was used to compare the physical fitness of indigenous and non-indigenous students. The test battery included six test items i.e. pull-ups, sit-ups, standing broad jump, shuttle run, 50-yard dash and 600-yard run-walk. For the comparison of fitness score, mean, SD, CV and Z-test were applied. Fitness status was found better among indigenous students in comparison to non-indigenous students.